EFEKTIFITAS FLIPPED CLASSROOM TERHADAP AKTIFITAS DAN HASIL BELAJAR BAHASA INDONESIA DI SEKOLAH DASAR - Lestari, Wahyu Wiji; Pratiwi, Cerianing Putri; Sundari, Etik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Students' learning readiness greatly influences students' activeness and learning outcomes. Students who are not ready to learn at school can be seen from the lack of student activity in learning activities and the low learning outcomes of students. Based on the results of interviews with students, it is known that they did not prepare the material that will be studied tomorrow at school. Many students spend their time at home playing games on their cell phones. Therefore, the Flipped Classroom method is applied in learning to find out how effective this method is in increasing student activity in learning activities and student learning outcomes. The method used in this research is quasi-experimental research which does not randomly assign subjects to either the experimental group or the control group. In this quasi-experimental research, the researcher used a One Group Time Series Design research design, where this research only used one sample group without using a comparison group. Based on the results of data analysis, it is known that the implementation of the flipped classroom is effective in increasing students' understanding in Indonesian language subjects in class IV at SDN 02 Manisrejo for the 2023/2024 academic year.